Synthesis of Ag-PVA and Ag-PVA/PET-s20 composites by supercritical CO2 method and study of silver nanoparticle growth - Silva,Rafael (2008)
Supercritical CO2 has been used to prepare silver polymer composites, silver/poly(vinyl alcohol) and silver/poly(vinyl alcohol)/sulfonated poly(ethylene terephthalate) through impregnation of a silver precursor in solid-state polymeric matrices followed by thermal reduction of the silver precursor. X-ray diffraction, scanning electron microscopy, energy dispersive spectroscopy, atomic force microscopy, thermogravimetric analysis and UV/vis spectroscopy indicate that synthesis conditions and polymeric matrix composition affect silver particle size, shape and distribution in polymeric matrices. Silver particles are smaller, have a more uniform shape and present narrower size distribution in PVA-rich than in PETs-rich composites.